2020
DOI: 10.1038/s41598-020-69333-z
|View full text |Cite
|
Sign up to set email alerts
|

Haptoglobin polymorphism and prostate cancer mortality

Abstract: Prostate cancer is a common malignancy in men worldwide and it is known that oxidative stress is a risk factor for cancer development. A common functional haptoglobin (Hp) polymorphism, originating from a duplication of a gene segment spanning over two exons, results in three distinct phenotypes with different anti-oxidative capacities: Hp1-1, Hp1-2, and Hp2-2. The aim of the study was to investigate the relationship between this Hp polymorphism and prostate cancer mortality. The study was performed on 690 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Hemoglobin is a protein in red blood cells responsible for carrying oxygen from the lungs to various parts of the body and transporting carbon dioxide back to the lungs for exhalation[ 18 ]. Hemoglobin content is an important indicator of the body's oxygen transport capacity[ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hemoglobin is a protein in red blood cells responsible for carrying oxygen from the lungs to various parts of the body and transporting carbon dioxide back to the lungs for exhalation[ 18 ]. Hemoglobin content is an important indicator of the body's oxygen transport capacity[ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the lower levels of serum haptoglobin in thalassemic patients could be attributed to presence of different polymorphisms of the haptoglobin gene. Kaiser et al [7] found that people with Hp2-2 have the lowest concentrations of Hp, while those with Hp1-1 have the highest, and the ones with Hp2-1 have concentrations fall somewhere in between.…”
Section: Ragab Et Al [19]mentioning
confidence: 99%
“…Numerous studies indicate that an individual’s belonging to the Hp polymeric phenotype (Hp2-1 and, especially, Hp2-2) is associated with the risk of many common diseases: cardiovascular, autoimmune, infectious, atherosclerosis, stroke, diabetes, tuberculosis, epilepsy, diabetic nephropathy, diabetic retinopathy, malignant neoplasms, weakening of cognitive functions [ 33 36 , 51 53 ]. However, in the case of prostate cancer, the role of the phenotype has not been found [ 54 ]. An important site of Hp synthesis, apart from the liver, is the lungs.…”
Section: Basic Functions and Role Of The Hp Phenotypementioning
confidence: 99%